Fe-Al-Si-Type Iron Aluminides: On the Strengthening by Refractory Metals Borides - Vodičková, Věra; Švec, Martin; Hanus, Pavel; Bukovská, Šárka; Pazourková Prokopčáková, Petra (Materials (Basel, Switzerland), 2022)
The effect of boron addition into Fe-28Al-5Si-X (X = -, 2Mo, or 2Ti) on the structure and high-temperature yield stress was investigated. Generally, the alloying of binary Fe3Al-type iron aluminides by silicon significantly improves high-temperature mechanical properties by solid-solution strengthening. On the other hand, the workability and ductile properties at room or slightly elevated temperatures get worse with the increasing silicon content. Boron alloying together with titanium or molybdenum alloying is one of the ways to improve the workability of this type of alloy and, at the same time, ensure the formation of a sufficient amount of secondary phase particles required for effective strengthening. In this paper, the influence of 1 at. % of boron on high-temperature yield stress is evaluated in response to structural changes and compared with results obtained previously on the same type of alloy (Fe-28Al-5Si-2X, X= -, Mo, or Ti) but without boron alloying. It can be concluded that the network structure of borides of refractory metals formed due to boron alloying works more effectively for alloy hardening at higher temperatures than a mixture of silicides and carbides present in the boron-free alloy of the same composition.
Keywords: Fe3Al-based cast iron aluminide; grain size; heat treatment; high-temperature yield stress; titanium; molybdenum and boron addition